DIGITALISASI DAN POLA KERJA BARU: DAMPAK BAGI INDUSTRIALISASI DAN RESPONS KEBIJAKAN KETENAGAKERJAAN - Fuat Edi Kurniawan; Norman Luther Aruan (Jurnal Sosioteknologi, 2021)
This article attempts to decipher claims about the ‘future of work’ based on the development of digitalization and look atthe policy response to those claims. Specifically, it explains the main developments of new digital technologies that shapejobs and employment in the context of Industry 4.0 and the emergence of various digital platforms. Digitalization alsohas an impact on the industrialization process to predict the loss of old manufacturing jobs. This is projected to disruptthe workforce that is at risk of new work patterns and dehumanization. This article is prepared using a qualitative methodwith a literature study approach, which aims to build a critical analysis of digitalization and its impact on labor andindustrialization policies. The results of this study indicate several industrialization policy responses at the global andnational levels for each digital development model. This study confirms that digital technology will not deterministicallyform a new future but the choices and logical consequences of a digital work pattern model that is different from the oldpattern. So, the industrialization policy response in the digital era must be able to answer the wave of disruption for theworkforce. Policies in the education and training aspects of the affected workforce are an urgency that cannot be ignoredin the era of industrial automation